Insilico study of Phyllanthus niruri potency as an antiviral Sars Cov 2: Omicron and delta variants : Analisis Potensi Phyllanthus niruri sebagai antivirus Sars Cov 2: varian Omicron dan delta secara insilico - Mushlih , Miftahul; Aliviameita, Andika; Puspitasari; Firmansyah, Nukayo; Murosidah, Pratasya Liyaajul (Universitas Muhammadiyah Sidoarjo, 2022)
Corona Virus Disease 19 (Covid 19) caused by infection with severe acute respiratory syndrome coronavirus 2 (Sars Cov-2). In its development, this virus has several variants due to mutations, including the Omicron (B.1.1.529) and delta (B.1.617.2) variants of concern, one of the keys to infection with this virus is the angiotensin receptor enzyme 2 (ACE-2). This study aimed to explore the potential of Phyllanthus niruri plant insilico. The active plant components were explored from the KNackSAcK family, then selected using Lipinski criteria using SWISS ADME, docking using HEX 8.0. The results of the analysis showed that 5 of the 21 compounds met Lipinski's criteria, i.e Hypophyllanthin, Hinokinin, 4-Methoxynorsecurinine, Nirtetralin, & Lintetralin. Nirtetralin & 4-Methoxynorsecurinine were able to change the binding conformation of RBD-ACE2 in the Omicron variant, while Hinokinin was able to change the binding conformation of RBD-ACE2 in the delta variant. These results were different from the first discovered sars cov 2, in which Hinokinin, 4-Methoxynorsecurinine, & Nirtetralin were able to change the conformation of RBD-ACE2.